RETRACTED: Engaging the citizen in the circular economy: Transcending the passive consumer role - Milios, Leonidas (Frontiers in Sustainability, 2022)
The transition to a resource-efficient and effective circular economy (CE) requires the active engagement of all societal and economic actors, including business, civic society, and political actors. Research, so far, has mainly focused on business solutions and policy approaches that enable these solutions. However, very little knowledge has been developed regarding the role of citizens in the CE (e.g. sharer, repairer, or buyer of quality products or second-hand products) and the transformations to everyday life that circularity may require. Therefore, there is an imperative to fill this knowledge gap and provide the insights needed to drive the adoption and upscale of circular practices in the everyday life of citizens. To go beyond existing approaches of consumer research, this contribution proposes the expansion of the methodological arena by integrating theories of socio-cultural (e.g. practice theory, consumption work) and psycho-social (e.g. peer-influence, social proof) nature to complement existing approaches of ‘behavioural’ scope, which have been widely used in economics and policy studies. By identifying the way people relate to CE in their everyday life and the conscious and unconscious actions they are likely to take towards a CE transformation, it is possible to complement the existing knowledge on CE business model innovation and policy interventions so that the ‘consumer’ aspect is better incorporated and not taken simply for granted, as a CE adopter.